Longevity of Ulmus pumila L. in protective afforestation on semi-desert lands of the Astrakhan Zavolzhye - Vladimir Vasilievich Lepesko; Ludmila Petrovna Rybashlykova (RUDN Journal of Agronomy and Animal Industries, 2021)
The article provides a predictive assessment of longevity of Ulmus pumila L. stands in the Astrakhan Zavolzhye. The effi and expediency of renewable logging for rejuvenation and increasing the longevity of plantings in the semi-desert were confi The classifi of ecotopes of the Astrakhan Zavolzhye on suitability for cultivation of protective and shadow elm plantings on pasture lands was developed and presented. In the Caspian region, Ulmus pumila became widespread in forest reclamation of semi-desert lands in the 1950s. Since then, till the beginning of the 1990s, Bogdinskaya research agroforestry experimental station laid on the sandy massifs about 1 thousand hectares of Ulmus pumila L. plantings, which currently amounts to 1824 %. The long-term practice of using protective shade Ulmus pumila umbrellas has shown their signifi ecological effect on functioning pastures. The aim of the research was to develop an improved technology for creating long-lived protective shade stands of Ulmus pumila on degraded pastures of the Astrakhan Zavolzhye. The research was carried out using generally accepted methods of stand forest taxation by A.P. Anuchin (1961), 1. Bitvinskas (1974) and A.S. Manaenkov (2001). Soil conditions were studied by drilling sounding to 3 m depth. The results of the research revealed that the longevity of wood species in the dry-steppe zone was determined mainly by two factors: productive moisture in the soil and salinity level. The most favorable growing conditions for Ulmus pumila were unsalted (to a depth of at least 3 m) brown sandy soils, sandy loam soils, dark-colored swale soils with periodic redistributed accumulation of moisture. In arid conditions of the Astrakhan Zavolzhye in island plantations (group of trees, umbrellas, 0.51 ha parts of forest area) and optimal growing conditions without logging and reforestation, Ulmus pumila lives up to 6070 years.